New Technologies, New Formalisms for Historians: The 3D Virtual Buildings Project. - Bonnett, John (Literary & Linguistic Computing, 2004)
In the coming decades, the platforms and formalisms scholars employ to display, transform, and transmit information will continue to evolve. Innovations in information management did not stop with the codex. They will not stop with the PC. The purpose of this paper is to explore a specific implication that new paradigms of computing-especially those pertaining to 3D objects and 3D environments-will present for the discipline of history. Put simply, this study suggests historians will need to re-think the aesthetics of their discipline. Drawing on the experience of the 3D Virtual Buildings Project, it suggests there are two possibilities historians can and ought to explore. The first is to test the efficacy of 3D objects as cognitive tools, tools designed to assist student realization that historical works are models, models that must be distinguished from the objects they represent. The second is to explore the use of 3D-immersive environments as platforms to display research findings. If Virtual Reality is to emerge as a viable medium for the historical discipline, scholars will need to transform their practice. Assumptions regarding the constitution of narrative, authorship and the scholarly work will all require modification.